1984
DOI: 10.1152/ajpregu.1984.247.3.r582
|View full text |Cite
|
Sign up to set email alerts
|

Blood-brain barrier transport and brain sequestration of propranolol and lidocaine

Abstract: Lipophilic amine drugs such as propranolol and lidocaine are actively sequestered by tissues via saturable cytoplasmic binding systems. The present studies were designed to characterize the kinetics of drug transport and sequestration in rat brain in vivo by using the carotid injection technique. Both propranolol and lidocaine are sequestered by brain, and the half time (t 1/2) of clearance of the drugs from brain to blood is 6-7 min. The t 1/2 of propranolol association and dissociation reactions with the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…7) This observation is in agreement with the effect of pH for cationic drugs such as lidocaine, mepyramine or propranolol using in vivo carotid injection technique. 14,15) The concentration-dependent uptake of PTZ at pH 5.5 showed the participation of a saturable uptake process (Fig. 3).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…7) This observation is in agreement with the effect of pH for cationic drugs such as lidocaine, mepyramine or propranolol using in vivo carotid injection technique. 14,15) The concentration-dependent uptake of PTZ at pH 5.5 showed the participation of a saturable uptake process (Fig. 3).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, PTZ is transported into the brain predominantly by a carrier-mediated mechanism. It was reported that the saturable BBB influx transport of cationic drugs showed an apparent low-affinity system for propranolol (K t ϭ9.8 mM) 14) or mepyramine (K t ϭ4.4 mM), 15) using the in vivo carotid injection technique. When the uptake of PTZ was measured by the in situ brain perfusion technique, the apparent influx transport of PTZ was saturable, with a K m value of 2.9 mM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the test compounds, the extraction at 15 s is not significantly different from the initial extraction. Owing to active sequestration mechanisms in the brain for the steroid hormones and for propranolol, the half-life of ligand distribution in brain after a pulse injection is 4-6 min (14,15). Therefore, the ligand efflux to blood in 15 s is <5%.…”
Section: Methodsmentioning
confidence: 99%
“…(1982) found that brain ex traction of IMP was decreased from a value of 92 to 74% when the arterial blood pH was lowered from 7.35 to 7.10. Pardridge's group proposed that this may be a pH effect (Pardridge and Fierer, 1985) since amphetamine(s) as well as other lipophilic basic amines are transported through the blood brain barrier substantially more slowly at lower pH (Pardridge and Connor, 1973;Pardridge et al, 1984). Therefore, it appears that LCBF measure ments with IMP as tracer should be further vali dated under conditions associating high CBF with low arterial blood pH, e.g., during respiratory aci dosis.…”
Section: Possible Pitfalls In Using Radioactive Imp For Lcbf Measuremmentioning
confidence: 99%